Models of terminological collocations in medical English discourse - Oksana O. Lyamova (Sovremennye Issledovaniâ Socialʹnyh Problem)
Background. The term "collocation" has recently come into use and become popular in modern linguistics, denoting the phenomenon that exists in all languages. Collocations are set expressions formed when one of the words composing the combination preserves its lexical meaning and the other changes it.